Publicly Traded Debt Restructuring Methods, Corporate Investment, and Debt Contracting - Fan, Xin (Management Science, 2025)
I use an important ruling, Marblegate Asset Management v. Education Management Corporation (EMC), to study the economic role of two publicly traded debt restructuring methods: coercive bond exchange offers and Chapter 11. This ruling restricted firms from employing coercive bond exchange offers to facilitate out-of-court restructurings, thereby increasing the likelihood of restructuring publicly traded debt under Chapter 11. Following the ruling, investment in affected distressed firms decreased substantially, but investment efficiency improved. The changes in covenant, maturity, and offering yield of newly issued bonds suggested that existing bondholders with covenants gained more bargaining power than shareholders and new bondholders. The paper provides causal evidence from a large sample analysis, demonstrating the divergent effects of these two publicly traded debt restructuring methods on investment policies. This paper was accepted by Victoria Ivashina, finance. Funding: Funding for this research was provided by University of Pittsburgh (Doctoral Fellowship) and Vanderbilt University (standard research funds). Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.01831 .